IMPACT OF 5E VS. TRADITIONAL TEACHING ON STUDENTS’ GEOGRAPHY INTEREST AND ACHIEVEMENT - Rao, Priyanka (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This research aims to determine the efficacy of the 5E Instructional Model as against the conventional approach to education on 9th-grade students’ interest, spatial intelligence, and academic achievement in geography in Hyderabad District, Telangana. The strategies under scrutiny include the 5E model, which is based on the Engage, Explore, Explain, Elaborate, and Evaluate phases, as compared to traditional approaches to learning, namely, lectures. Since both pretest and posttest were given to the students, and they were 100 in number and divided into two groups, 50 each, their interest in geography, spatial intelligence, and academic performance were rated. According to the result, there is no significant difference on the view or interest of the students whether taking Rote learning method or Meaningful learning method on the given posttest. Also, in the spatial intelligence aspect, the mean scores of the two groups proved almost equal. However, based on the theoretical underpinnings of the moded and the 5E model the study show that some factors such as prior knowledge, external influences, duration of the interventional affected the outcomes. The study indicates that there is a requirement to establish the efficiency of the concept of active learning models as a way of enhancing the long-term interest of the students and the spatial intelligence when teaching this Geography course.